K-Chart: a tool for research planning and monitoring - Mohd Khazani Abdullah,; Nur Riza Mohd Suradi,; Nordin Jamaluddin,; Ahmad Samsuri Mokhtar,; A. Rahim Abu Talib ,; Mohd Faizal Zainuddin, (Penerbit ukm, 2006)
The importance of planning and monitoring in any activities, more particularly researches can never be over-emphasized. Inadequate research planning and monitoring leads to delayed delivery of results, inefficient use of resources and increased cost. There are various research tools available and being used to assist in research planning and monitoring. An efficient tool should address the issues under study, the methodologies used, the expected results in sufficient details, the timelines, and monitoring features. However, there is arguably no existing tool that can support all the features individually. In this paper, a new research planning and monitoring tool, K-chart is proposed. K-chart provides all the features mentioned above and presents them in a simple way. This paper elaborates on the construction of K-chart and its advantages